QARÍM-QATNAS HÁM ShAXSLAR ARALÍQ MUNÁSIBETLERDIŃ INSAN RAWAJLANÍWÍNDAǴÍ ORNÍ - Sariev, Rawshanbek Yusupovich (ILIM hám JÁMIYET, 2026)
This article analyzes the importance of communication and interpersonal relationships in human personality development, their influence on the socialization process, and their role in the formation of communicative skills. The importance of effective communication in personal and professional activities is also highlighted.